Stakeholders Perception about Bt Cotton and Related Socio-economic Implications and Bio-safety Concerns - Surya, S.; Padaria, R.N.; Singh, Baldeo; Ram, Leela; Pankaj, Pankaj (Indian Journal of Extension Education, 2022)
Unprecedented rates of diffusion and adoption of Bt cotton have demonstrated its relative advantage as well as acceptance among million of farmers engaged in cotton cultivation. However, the prevailing apprehensions, misconception, ill information based perception and risk concern has led to development to protest group against transgenic crop. Hence the present study was conducted in states of Punjab of Karnataka to examine the perception among different stakeholders about Bt cotton and related issues of socio economic implications and bio-safety. A majority of farmers held positive perception about transgenic cotton (Bt cotton) due to its highly satisfactory performance in terms of higher yield, low requirement of pesticide and labours besides reduced pesticide related pollution and health hazards. The extension worker as well as the scientist engaged in the transgenic research too had positive perception about transgenic technology. Perception about Bt technology and related socio-economic implications differed highly significant (P<0.01) with two sets of farmers i.e. with Bt cotton and without Bt cotton.